Identifying long term patterns and drivers of vegetation structure in an African savanna using stable carbon and nitrogen isotopes - Ghaui, Mark (Department of Biological Sciences, 2017)
Savanna systems are complex and dynamic in space and time. Climate, fire, herbivory and nutrients have been identified as structuring agents of savanna form and function, but their interactions and feedbacks with one another and vegetation are poorly resolved. Increasing the spatial and temporal scope of studies will help to improve this situation, as demonstrated in recent studies in the spatial dimension in particular. This study aims to investigate vegetation and Nitrogen cycling changes over time in a diverse patch mosaic landscape in Hluhluwe-iMfolozi Park to identify drivers of vegetation structure and their dynamism over time. Sediment from a 150cm core (taken using a Russian corer) was analyzed for stable ¹³C and ¹⁵N isotope abundances, and C:N ratio of soil organic matter. The base of the core was dated at 2380±40cal.Yr.BP. δ¹³C, δ¹⁵N and C:N of soil organic matter was found to be variable over time. δ¹³C followed a pattern of stable periods of distinct abundance separated by abrupt changes; δ¹⁵N and C:N underwent changes over the same periods as δ¹³C. Vegetation follows a pattern of phase and transition as predicted by resilience theory. An aquatic vegetation phase persists around 2000cal.Yr.BP to about 500cal.Yr.BP, coinciding with a warm, wet period (including the Medieval Warm Period) with an open Nitrogen cycle. A C₄ grassland phase follows alter a transition to cool, dry conditions coinciding with the Little Ice Age, and decreasing openness of the N cycle. Recent increasing C₃ vegetation and N-openness were attributed to atmospheric CO₂ increase and Nitrogen deposition respectively. Climate is concluded to be the major driver of vegetation at this site, and a combination of climate and vegetation are responsible for changes in Nitrogen availability. Findings are discussed in relation to landscape management. Multi-proxy evidence in future studies would be useful in validating the findings of this study.